The Impact of Suspect Resistance, Informational Justice, and Interpersonal Justice on Time Until Police Use of Physical Force: A Survival Analysis - Piza, Eric L. (Crime & delinquency, 2024)
The current study applies Systematic Social observation (SSO) to body-worn camera (BWC) footage of use of physical force events in Newark, NJ. The analysis tests the effect of suspect resistance and police officer interpersonal and informational justice tactics on time until use of physical force in police-citizen encounters. The results indicate police officer actions have a greater effect on the time until physical force than does suspect resistance. Officer adherence to informational justice is negatively associated to the time until both first use of force and highest level of force. Suspect resistance did not achieve statistical significance in any model. This study has implications for research and police practice, and demonstrates the benefits of leveraging video footage in criminological research.